Produtividade, características vegetativas e composição nutricional dofeno de amendoim forrageiro - Thiago Meireles Félix (2012)
This study aimed to evaluate the vegetative characteristics, productivity and nutritional composition of hay of Arachis pintoi, cut every forty days, during a year in Montes Claros, Minas Gerais. It was used five beds with 3.99 m² each. It was performed nine successive cuts (C), being 17/06 (C1), 27/07 (C2), 06/09 (C3), 16/10 (C4), 26/11 (C5) in 2008, and 08 / 01 (C6), 16/02 (C7), 06/04 (C8) and 16/05 (C9) in 2009. The legume was cut manually, close to the ground. In 20 plants per beds was measured: plant length, number of leaves and number of stems and relation leaf / stem. The plant material was cut and heavy and the haymaking made in the sun on canvas. The hays were weighed and stored in a place covered, dry and protected from light. Samples milled to 1 mm to determine the levels of dry matter (DM), neutral detergent fiber (NDF), acid detergent fiber (ADF), crude protein (CP), mineral matter (MM) and lignin; evaluate the digestibility in vitroof dry matter (IVDMD) and degradability in situof dry matter (DISDM). The experimental design was totally randomized with nine treatments (cuts) and five replications (beds). Data from vegetative characteristics subjected to analysis of variance and the Scott-Knott test (p 0.01). The extrapolated average production (tha -1) of green mass, mass into hay and dry matter ranged from 7.62 to 20.51, 2.00 to 3.35, and 1.82 to 3.20, respectively. The length ofthe stems, the average per plant, the average number of stems per plant and the relation leaf / stem ranged statistically from 3.60 to 11.88, 1.00 to 1.24, 1.99 to 3.83, and 1.80 to 3.83 respectively. The averages of NDF, ADF, MM, lignin and IVDMD were submitted to the Scott-Knott test (p 0.05). The values of NDF, ADF, and IVDMD MM differed ranging from 36.72 to 42.71%, 16.21 to 19.45%, 14.68 to 20.69%, 1.22 to 2.00%, and 75.18 to 84.13%, respectively. In the DISDM of hay formed poolsof drought and rainfall, composed respectively by the cuts: C1, C2, C3, C4 and C6, C7 and C8. It was used one gram in each pool in polypropylene envelopes, put into the rumen of fistulated cattle. It were analyzed Samples taken at 0, 6, 12, 24, 48, 72 and 96h. Hays obtained during the dry and rainy the potential degradabilities in situranged from 86.84 and 84.36%, respectively. Showed up larger plants in January and February, the biggest development in the rainy period is justified by the interference of precipitation and luminosity in the growth of this tropical forage. The forage hay cut every 40 days under the conditions of Montes Claros, presented good nutritional characteristics and high IVDMD and DISDM indicating its recommendation zootechnical, especially in periods of scarcity of fodder.